Photoshop Elements 12 all-in-one for dummies - Obermeier, Barbara; Padova, Ted (--For dummies., 2014)
Explores filters, effects, styles, and distortions. Shows you how to enhance your images by painting, drawing, and typing. Walks you through working with layers and masks. Details ways to retouch and enhance your photos. Checks out the toolbox, options, and other essential menus.